Divided We Fall. Conflicts of Interests Regarding Fiscal Discipline in Municipal Hierarchies - Lina Maria Ellegård (Lund University, School of Economics and Management, Department of Economics, 2013)
Persistent budget deficits are commonly blamed on irresponsible governments. However, even if the government is fiscally responsible, the agents in charge of implementing the budget may be less concerned about fiscal discipline. According to the survey data analyzed in this paper, such conflicts of interests are associated with low fiscal performance and prevail in almost half of the Swedish municipalities. The empirical analysis points at some organizational features that may affect the prevalence of conflicts, and also indicates that conflicts may arise for reasons exogenous to the organization.
Keywords: D23; D71; D73; D74; D78; 330; local governments; fiscal discipline; conflict of interests; organization